2016
DOI: 10.1111/1745-9125.12111
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for Collective Deviance: Group Size and Changes in Perceived Risk, Cost, and Reward*

Abstract: Research has demonstrated that the presence of others shifts decision‐making about risky/deviant behavior. One reason for this shift could be changes in the anticipated experience of formal sanctions, informal costs, and rewards. To investigate this possibility, this study conducted two randomized controlled trials with hypothetical vignettes, in which a range of how many other people were also involved in the criminal act defined the treatment conditions. Across two samples of university students (Ns = 396 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 89 publications
5
83
0
Order By: Relevance
“…Research in social psychology has shown that the presence of others decreases individual's (public) self-awareness and enhances feelings of anonymity (Diener, 1976;Festinger et al, 1952;Postmes & Spears, 1998;Prentice-Dunn & Rogers, 1982). Within criminology, McGloin and Thomas (2016a) illustrated that the number of co-offenders was related to individuals' anticipated sanction risk (see also Matthews & Agnew, 2008).…”
Section: Passive Peer Influencementioning
confidence: 99%
See 3 more Smart Citations
“…Research in social psychology has shown that the presence of others decreases individual's (public) self-awareness and enhances feelings of anonymity (Diener, 1976;Festinger et al, 1952;Postmes & Spears, 1998;Prentice-Dunn & Rogers, 1982). Within criminology, McGloin and Thomas (2016a) illustrated that the number of co-offenders was related to individuals' anticipated sanction risk (see also Matthews & Agnew, 2008).…”
Section: Passive Peer Influencementioning
confidence: 99%
“…Fourth, the presence of others may reduce (perceived) informal costs such as feelings of responsibility, shame, or guilt. Scholars have argued that these feelings should be considered as internal costs or "self-imposed punishments" in the offender decision-making process (Grasmick & Bursik, 1990;McGloin & Thomas, 2016a;Nagin & Paternoster, 1993). When acting in a group, individuals are said to experience a psychological state in which an individual becomes one with the group, also referred to as "deindividuation" (Diener, 1976;Festinger et al, 1952;Postmes & Spears, 1998;Prentice-Dunn & Rogers, 1982).…”
Section: Passive Peer Influencementioning
confidence: 99%
See 2 more Smart Citations
“…(: 271) explained, “people's emotional reactions to risks depend on a variety of factors that influence cognitive evaluations of risk only weakly or not at all.” For example, sexual arousal or intoxication may directly reduce fear. Likewise, the presence of co‐offenders may directly reduce fear, as well as indirectly reduce fear by lessening perceived risk (McGloin and Thomas, ). Situational risk and fear should then influence situational offending decisions, with fear having a more proximate and powerful effect than risk (Loewenstein et al., ).…”
Section: Fear and Deterrence: Situational Offending And Criminal Propmentioning
confidence: 99%